Changes in Childhood Body‐Mass Index and Risk of Venous Thromboembolism in Adulthood - Jens Sundbøll; Lars Ängquist; Kasper Adelborg; Line Klingen Gjærde; Anne Ording; Thorkild I. A. Sørensen; Jennifer L. Baker; Henrik Toft Sørensen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Childhood weight trajectories may influence cardiometabolic traits and thereby the risk of venous thromboembolism (VTE) later in life. We examined whether overweight and changes in weight status during childhood were associated with risk of VTE in adulthood. Methods and Results We used Danish medical registries to conduct a population‐based cohort study of Danish schoolchildren aged 7 to 13 years and born during 1930‐1989. We calculated body‐mass index (BMI) z‐scores based on weight and height measurements. We estimated hazard ratios using Cox regressions to examine associations between changes in BMI z‐scores from 7 to 13 years of age and the subsequent risk of VTE. Among 313 998 children, 5007 girls and 5397 boys were diagnosed with VTE as adults. Compared with children with a normal BMI (25th to 75th percentile category) at both ages, children with a BMI persistently above the 75th percentile had a 1.30‐ to 1.50‐fold increased risk of VTE in adulthood. Children who experienced a BMI increase from the 25th to 75th or >75th to 90th percentile to a higher percentile category had a 1.35‐ to 1.70‐fold increased risk of adulthood VTE. Children whose BMI percentile category decreased between 7 and 13 years of age had a VTE risk similar to that of children with a persistently normal BMI. Conclusions Risk of VTE in adulthood was higher in children with a persistently above‐average BMI. Whereas weight gain from 7 to 13 years of age additionally increased VTE risk, remission from overweight by 13 years of age completely reverted the risk.